The Relationship Between Duration of Hypertension and Serum Creatinine, Urea, and Estimated Glomerular Filtration Rate (EGFR) in Hypertensive Patients - Fitriana Fitriana; Hastuti Herman (Jurnal Indonesia Sosial Sains, 2026)
Hypertension, defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg, affects 34.1% of Indonesia's population according to the Indonesian Basic Health Research. Uncontrolled and long-standing high blood pressure can damage the glomerular structure, leading to decreased kidney function characterized by increased urea and creatinine levels, as well as a reduced glomerular filtration rate (eGFR), which is the main indicator for staging chronic kidney disease. The purpose of the study is to analyze the relationship between the duration of hypertension and kidney function biomarkers, namely creatinine, urea, and estimated glomerular filtration rate (eGFR), in hypertensive patients. This research method uses an observational analytical design with a purposive sampling technique, involving a total of 30 patients with grade 1 and grade 2 hypertension. The results of the examination of kidney function biomarkers (creatinine, urea, and eGFR) in relation to the duration of hypertension, based on the nonparametric Kendall's tau correlation test, showed no significant relationship between creatinine values and duration of hypertension (p = 0.061, p > 0.05), nor between urea values and duration of hypertension (p = 0.198, p > 0.05); however, a significant relationship was found between eGFR and duration of hypertension (p = 0.006, p < 0.05). Thus, it can be concluded that eGFR is a potential biomarker in laboratory examinations for assessing the risk of kidney damage complications in hypertensive patients. It is recommended that people with hypertension undergo regular kidney function checks in order to reduce the risk of long-term complications.